+0  
 
0
222
1
avatar

if x*y=x-(y*x)-y, find

(a) (-3)*(-5)   (b)  (-5)*(-3) (c)

From the above results, state if x*y=y*x.

Guest Aug 13, 2017
 #1
avatar+18 
+1

a) 

-3 × -5 = -3 - (-5 × -3) - -5

-3 × -5 = 15

-3 - (-5 × -3) - -5 = -3 - 15 - -5 = -13

15 ≠ -13 ∴ the equation is false

 

b) Just do the same prosses but swap the numbers

-5 × -3 = -5 - (-3 × -5) - -3

-5 × -3 = 15

-5 - (-3 × -5) - -3 = -5 - 15 - -3 = -17

15 ≠ -17 ∴ the equation is false

 

c) x*y=y*x is true, but I don't get how doing x*y=x-(y*x)-y is supposed to prove if x*y=y*x is true or false since they're different equations. 

LARAUJO  Aug 14, 2017

11 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.